INNOVATIVE APPROACHES TO CREATING AN INCLUSIVE ENVIRONMENT IN PRESCHOOL EDUCATIONAL INSTITUTIONS: LESSONS FROM THE EXPERIENCE OF EUROPEAN COUNTRIES - Mariia OLIINYK; Roksoliana KUSHNIRYK (Association of Social and Educational Innovation, 2024)
This article investigates innovative approaches to creating an inclusive environment in preschool educational institutions following the experience of European countries. It emphasizes the value of interdisciplinary cooperation, universal design for learning, and the application of modern technologies in order to meet the individual educational needs of children.